A hormone-to-neuropeptide pathway inhibits sexual receptivity in immature Drosophila females - Jie Chen; Peiwen Zhu; Sihui Jin; Zhaokun Zhang; Simei Jiang; Sheng Li; Suning Liu; Qionglin Peng; Yufeng Pan (Proceedings of the National Academy of Sciences, 2025)
Newborns, typically asexual, undergo a process of sexual transition to reach sexual maturity, but the regulatory mechanism underlying this transition is not clear. Here, we studied how female sexual behavior is modulated during sexual transition by hormones and neuromodulators in Drosophila . We found that neuropeptide Leucokinin (LK) inhibits female receptivity specifically during a sexual transition period in immature females, but not in younger or mature females. Moreover, the steroid hormone ecdysone, which is mainly synthesized in the female ovary during sexual maturation, acts on LK neurons via the ecdysone receptor to suppress sexual receptivity. We further found that LK suppresses female receptivity through its receptor LKR in central pC1 neurons, a decision center for female sexual behavior. These findings reveal a hormone-to-neuropeptide pathway that specifically inhibits sexual behavior during sexual maturation in female Drosophila , shedding light on how hormones and neuromodulators coordinate sexual development and behaviors.